Development of Noninvasive in Vivo Approach to Assess Vascular Permeability in Inflammation Using Fluorescence Imaging. Issue 6 (December 2018) - Shimazui, Takashi; Nakada, Taka-aki; Fujimura, Lisa; Sakamoto, Akemi; Hatano, Masahiko; Oda, Shigeto
ABSTRACT: Introduction: In vivo fluorescence imaging can quantify vascular permeability without requiring sacrifice of animals. However, use of this noninvasive approach for vascular permeability assessment in remote organ injury caused by systemic inflammatory disease has not been reported. Methods: Evans blue (EB) and Genhance 750 fluorescent dye were mixed and injected into mice. The lung as a remote organ and the footpad as a noninvasive observational site were assessed in a cecal ligation and puncture (CLP)-induced systemic inflammation mouse model and compared with sham and hydrocortisone pretreated (CLP + HC) mouse models. Extraction of EB in harvested tissues was assessed as a conventional indicator of vascular permeability. Fluorescent intensities in the footpad or harvested lung were assessed and their correlation was analyzed to investigate this novel, noninvasive approach for estimation of lung vascular permeability. Results: Fluorescent intensity in the footpad and harvested lung in the CLP group was significantly higher than in the other groups (footpad, sham vs. CLP, P < 0.0001; CLP vs. CLP + HC, P = 0.0004; sham vs. CLP + HC, P = 0.058; lung, sham vs. CLP, P < 0.0001; CLP vs. CLP + HC, P < 0.0001; sham vs. CLP + HC, P = 0.060). The fluorescent intensity in the footpad was strongly correlated with that in the lung ( r = 0.95). Conclusions: This fluorescent technique may be useful for vascular permeability assessment based on EB quantification. Footpad fluorescent intensity was strongly correlated with that in the lung, and may be a suitable indicator in noninvasive estimation of lung vascular permeability.